Influence of nutrient medium and time on lipopeptide synthesis in Bacillus subtilis GM5 - Lutfullina Guzel; Abubakirova Adela; Lutfullin Marat; Mardanova Ayslu (BIO Web of Conferences)
The level of expression of srfAD gene, a subunit AD of surfactin synthetase, and the yield of the total lipopeptide fraction were studied in relation to the composition of nutrient medium and the growth stage of the probiotic strain Bacillus subtilis GM5. The maximum concentration of the total lipopeptide fraction was observed during the growth of strain GM5 on SMN medium with soybean flour. The relative expression of the srfAD gene of B. subtilis GM5 was quantified by RT- qPCR. We conclude that the increase in the concentration of the total lipopeptide fraction on SMN medium correlates with the expression of the srfAD gene during 96-hour cultivation of GM5, which may indicate the production of mainly lipopeptide from the surfactin group by under these conditions.